Estimation of demographic population parameters using non-invasive methods in woodland caribou (Rangifer tarandus caribou) - McFarlane, Samantha (2015)
Demographic population parameters of woodland caribou were estimated using non-invasive fecal sampling. Fecal pellet sampling occurred in several woodland caribou populations from 2004 to 2013. Samples were amplified at 10 microsatellite loci and unique individuals identified. We used fecal pellet reproductive hormones levels and pellet dry weight to differentiate calf from adult age-classes. Results demonstrate that pellet weight, pregnane, and testosterone were able to identify age-classes which were used in capture-mark-recapture analysis in program MARK. In addition, we estimated effective population size of woodland caribou using linkage disequilibrium, sibship assignment and temporal methods. Results demonstrate that the linkage disequilibrium method produces precise estimates, and a reduced number of loci or number of unique genotypes produced precise estimates. This study demonstrates the power of non-invasive fecal sampling for determining age-classes and estimating demographic population parameters of woodland caribou, with potential for use in other populations or species. October 2015